Anti-HSP90 autoantibodies in sera of infertile women identify a dominant, conserved epitope EP6 (380-389) of HSP90 beta protein - Idicula-Thomas Susan; Choudhury Asmita K; Pires Eusebio S; Khole Vrinda V (BMC, 2011)
Abstract Background We earlier reported a simple specific test for detection of anti-ovarian antibodies in infertile women and identified number of specific molecular and cellular targets of which human heat shock protein 90-beta (HSP90 beta) was found to be the most immunodominant. The present study focuses on prediction and validation of the immunodominant epitope/s of this protein using sera from infertile women having anti-HSP90 autoantibodies. Methods Delineation of the immunodominant epitopes of HSP90 beta was done by using epitope prediction algorithms and 10 peptides (EP1-EP10) were custom synthesized. Their immunoreactivity was measured by ELISA using sera from patients and controls. To determine the most immunodominant epitope, the results were subjected to statistical analysis. The immunoreactivity of the immunodominant peptides were confirmed by dot blots using sera from patients. A rabbit polyclonal antibody against the immunodominant epitope was generated and its immunoreactivity to the parent protein in ovarian extracts as well in oocytes and embryos was investigated. Results Experimentally and statistically, peptide EP6 (380-389) seems to be the major antigenic epitope for the serum antibody binding followed by EP1 (1-12) and EP8 (488-498). Predicted 3D structures of these peptides demonstrated that they exist in the loop conformation which is the most mobile part of the protein. Also, analysis of the sequences of HSP90 beta across several species reveals that EP6 peptide forms a part of a well conserved motif. The polyclonal antibody generated to the immunodominant epitope- EP6 confirms similar biochemical and cellular immunoreactivity as seen with the patients' sera having anti-HSP90 autoantibodies. Conclusions The decapeptide EP6 is a major immunogenic epitope of HSP90 followed by EP1 and EP8. Knowledge of binding epitopes on the autoantigen is necessary to understand the subsequent pathologic events. The study might generate new tools for the detection of disease-inducing epitopes and a possible therapeutic intervention.